Russia : Financial Sector Assessment - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) is a summary of some of the findings of the Financial Sector Assessment Program (FSAP) report for the Russian Federation, which was prepared jointly by the International Monetary Fund (IMF) and the Bank in close cooperation with the Russian authorities. Given the small size of the financial sector, the effects of a potential financial sector distress on the macro-economy would be relatively small. However, there are serious weaknesses in the financial sector per se, hampering the development of the sector, and its ability to allocate resources in the Russian economy. A few interlinked issues cut across the banking, capital markets, and the insurance sectors. In spite of recent improvements, the lack of transparency in the ownership structures, and poor corporate governance, including banks, slowed down the development of the sector, and hindered financial decisions, and prudential supervision. There has been progress in implementing structural reforms in key areas, e.g., the agricultural land market, pension funds, and small business taxation - but other reforms, including in the financial sector, have lagged behind. While banks in Russia appear to be well capitalized, the quality of capital is questionable, even under the Russian Accounting Standards (RAS), and, loan provisioning does not fully reflect the banks' credit risks. Thus, banking sector reform is a matter of the highest priority, if Russia is to achieve its growth potential in the coming years. Reform efforts should be concentrated on strengthening the supervisory framework; enhancing the transparency of ownership, governance, and financial reporting; and, facilitating the consolidation of the fragmented private banks, as well as leveling the playing field between private, and state banks. Most importantly, any strategy for promoting the development of the banking sector, will need to carefully consider the role of Sberbank. The legal infrastructure for the banking sector is generally well developed, but supporting legislation and regulation for banking supervision and implementation practices needs to be improved.